Desmoid-type fibromatosis of the breast with positive margins: a case report and review of conservative management - Alqathami, Ghiad F.; Alsharif, Nejoud; Alqasqari, Khairiah Y. (International Surgery Journal, 2025)
Breast desmoid-type fibromatosis (BDF) is a rare, benign, but locally aggressive tumor that mimics breast carcinoma. Management has shifted toward conservative strategies, including active surveillance, especially for asymptomatic or indolent lesions. A 29-year-old woman presented with a 2 cm firm, immobile mass in the left inframammary fold. Ultrasound and magnetic resonance imaging (MRI) revealed an irregular hypoechoic lesion. Core needle biopsy showed spindle cell proliferation. Wide local excision confirmed desmoid-type fibromatosis, with nuclear β-catenin and SMA positivity, CD34 and S-100 negativity, and Ki-67 <5%. The superior margin was positive, while other margins were clear. Considering the low proliferative index and absence of aggressive features, the patient was managed with active surveillance and regular clinical and radiological follow-up. BDF can be safely monitored in selected patients, even with positive margins, avoiding unnecessary surgery while ensuring close follow-up for progression.